Relationship between demographic factors, social support and sociocultural adjustment among international post graduate students in a Malaysian public university - Abdullah, Maria Chong; Adebayo, Areo Sunday; Talib, Abd Rahim (Richtmann Publishing, 2015)
This study examined the relationship between demographic factors, social support and sociocultural adjustment among international post graduate students enrolled in a Malaysian public university. A descriptive correlational research design was utilized to address the research objectives. A total of 150 international students studying in the faculty of educational studies in one of the public university in Malaysia participated in the study. Two research instruments were used to collect the research data. The Multidimensional Scale of perceived social support was used to assess the level of social support perceived by the respondents, while the Socio-cultural Adaptation Scale was used to measure international students’ level of sociocultural adjustment. Demographic information such as gender, marital status, and year of study were also collected. Findings show that the respondents have a moderate level of socio-cultural adjustment (M=2.38). The results of independent sample t-test show that there were no significant differences in the level sociocultural adjustment based gender (t[150]=-1.50, p>.05), marital status (F[2, 147]=1.18, p=.31), and year of study (F[3, 146]=.37, p=.78). The result of simple linear regression analysis reveals that social support significantly (β=.27, p=.001; R2=.07) predicts students’ sociocultural adjustment. Lastly, specific adjustment difficulties reported by the international students were found to be related to making friends, communication, transportation, accommodation, food, job, climate, and time differences. In this study, we can conclude that social support from family, friends and significant others is the key indicator of international student’s sociocultural adjustment in Malaysia. Implications of the study and suggestions were also discussed.